2009
DOI: 10.1111/j.1399-0039.2009.01331.x
|View full text |Cite|
|
Sign up to set email alerts
|

HLA‐G polymorphism influences the susceptibility to HCV infection in sickle cell disease patients

Abstract: Despite its well known monogenic etiopathogenesis, sickle cell disease (SCD) is characterized by a striking variability of clinical presentation. There is growing evidence that genetic factors may be involved in this variability. Human leukocyte antigen (HLA)-G is a non-classical HLA molecule which was shown to be expressed at sites of inflammation and in inflammatory diseases. Besides its large and highly polymorphic promoter region, the 3' UTR region seems also to play an important role on regulating HLA-G e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 34 publications
0
46
0
3
Order By: Relevance
“…Roles of HLA-G expression induced by influenza A virus [21], human cytomegalovirus virus (HCMV) [22], human immunodeficiency virus (HIV) [23], HBV [24], and rabies virus [25] have been discussed. Recently, Cordero et al found that HLA-G polymorphism ϩ3142 (rs1063320) could influence the susceptibility to HCV infection in patients with sickle cell disease [26]; however, expression of HLA-G and its role in HCV infection are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Roles of HLA-G expression induced by influenza A virus [21], human cytomegalovirus virus (HCMV) [22], human immunodeficiency virus (HIV) [23], HBV [24], and rabies virus [25] have been discussed. Recently, Cordero et al found that HLA-G polymorphism ϩ3142 (rs1063320) could influence the susceptibility to HCV infection in patients with sickle cell disease [26]; however, expression of HLA-G and its role in HCV infection are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that polymorphic sites at the 3= untranslated region of the HLA-G gene, which are potentially associated with the magnitude of HLA-G production, have been associated with risk factors for the vertical transmission of HCV [13] and susceptibility to HCV infection in sickle cell disease patients [14]. Recently, Weng et al reported that plasma soluble HLA-G levels were dramatically altered in individuals with chronic HCV infection; however, expression of HLA-G in live and its role in HCV infection remain unknown [15].…”
Section: Introductionmentioning
confidence: 99%
“…Certain genotypes of the human leukocyte antigen (HLA) confer an increased susceptibility to infection or favor spontaneous viral clearance [30][31][32][33]. Early studies using normalization of ALT levels for six months after treatment end to define SVR found a positive association after interferon-monotherapy with HLA-DR2 in Egyptians (OR 9.495 [34]) and DRB1*0404 in Caucasians (DRB1*0404+: SVR = 25% vs. DRB1*0404À: SVR = 2.3% [35]).…”
Section: Major Histocompatibility Complexmentioning
confidence: 96%